Low-Dose Anti-PD(L)1 for the Treatment of Solid Malignancies - Iza Andrade de A. Souza; Beatriz de M. Dobbert; Barbara G. Sao Jose; Joao Pedro Homse-Netto; Larissa L. Furlan; Maira S. Abreu; Camila Ferrari; Bruno Uchoa; Kathia Abdallah; Stephano N. Lucio; Joao A. Soler; Fabio L.C. Fernandez; et al. (JCO Global Oncology)
PURPOSEMounting data suggest that lower doses of anti-PD(L)1 agents can be as efficacious as label-approved doses at a fraction of its cost. We compare the outcomes of patients treated with low-dose (LD) and with conventional-dose (CD) anti-PD(L)1 agents.METHODSThis observational study evaluates the outcomes of patients with solid malignancies treated with anti-PD(L)1 agents (LD or CD) at Hospital de Base, Brazil. Patients were classified as receiving LD if the dose administered in the first cycle was below the label-approved dose. Efficacy outcomes, including best clinical overall response rate (cORR), clinical progression-free survival (cPFS), and overall survival (OS), were evaluated.RESULTSFrom January 2020 to May 2023, 71 patients were included: 49 (69%) with LD and 22 (31%) with CD agents. The most frequent tumor sites were the lung (41% LD, 22.9% CD) and skin (melanoma; 24.6% LD, 50% CD). Most of the patients were treated with pembrolizumab (65% LD and 72% CD). The mean dose of pembrolizumab was 95.3 mg (1.5 mg/kg) in LD and 168.7 mg (2.12 mg/kg) in CD groups, once a day, q21d (every 21 days). After a median follow-up of 10.9 months, there were no significant differences between LD versus CD in cORR (38.1% v 35.2%, P = .31), cPFS (5.3 m v 7 m, P = .36), and OS (12.8 m v not reached, P = .17). A subgroup analysis with patients receiving pembrolizumab was performed, and similar results were obtained.CONCLUSIONOur study found no differences in cORR, cPFS, and OS between patients treated with LD and CD anti-PD(L)1. LD anti-PD(L)1 could be an alternative to promote accessibility, which warrants further investigation in randomized trials.